2023
DOI: 10.1088/1478-3975/acc301
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation reveals the effect of severing enzymes on dynamic and stabilized microtubules

Abstract: Microtubule severing enzymes Katanin and Spastin cut the microtubule (MT) into smaller fragments and are being studied extensively using in-vitro experiments due to their crucial role in different cancers and
neurodevelopmental disorders. It has been reported that the severing enzymes are either involved in increasing or decreasing the tubulin mass. Currently, there are a few analytical and computational models for MT amplification and severing. However, these models do not capture the action of microt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…We also note that although our study here is focused on tubulin-induced repair at damages created by severing proteins on microtubules, our model of damage spreading may be useful for analyzing other situations where reincorporation of new tubulin on a microtubule shaft has been observed, such as at sites of defects created by mechanical stress 46 , 56 or motor protein-induced damage 49 , 50 on microtubules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also note that although our study here is focused on tubulin-induced repair at damages created by severing proteins on microtubules, our model of damage spreading may be useful for analyzing other situations where reincorporation of new tubulin on a microtubule shaft has been observed, such as at sites of defects created by mechanical stress 46 , 56 or motor protein-induced damage 49 , 50 on microtubules.…”
Section: Discussionmentioning
confidence: 99%
“… 45 Further, in-vitro studies and computational studies have reported that severing proteins promote the regrowth of severed microtubules by enhancing the rate of rescue in microtubules 46 , 47 and lead to a net increase in microtubule number and mass. 20 , 28 , 29 , 48 , 49 It is unknown whether severing proteins have the same effect in vivo where they interact with other microtubule-associated proteins. Interestingly, incorporation of new tubulin dimers into microtubule lattice has also been reported at defects arising from mechanical stress, 46 , 47 or damages created by molecular motors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ATP hydrolysis-driven conformational changes of the hexameric ring enable it to exert force or produce motion that helps to remove the tubulin subunit from the MT 13 . Recently, discrete lattice-based Monte Carlo models incorporating microtubule (MT) dynamics and severing enzyme activity have been developed to elucidate the effects of severing enzymes on tubulin mass, MT quantity, and MT length 14 . However, the breaking and reorganization of MTs by the katanin play a crucial role in ciliogenesis 15 , cell size regulation 4 , plant cell wall biosynthesis and phototropism 16,17 .…”
Section: Introductionmentioning
confidence: 99%